Life and Scientific Activity of Sadrul-Islam Abul-Yusr Muhammad Pazdavi (421-493 AH/1027-1099 AD) - Shakir Shawkat ogli (Scientific Trends, 2024)
This article examines the scientific legacy of Abul-Yusr Pazdavi, an allama who has a unique place in the development of the doctrine of Moturidism, which is recognized as one of the two main directions of the Ahl-e-Sunna wal-Jamaa school of kalam in the Islamic world today. The representatives of the Pazdawi family have made great contributions to the development of the Hanafi legal sect and the doctrine of Moturidism, and by analyzing their activities and scientific heritage, new scientific conclusions can be obtained regarding the history of the development of these teachings and the influence of Pazdawi scholars on this process.
Keywords: Ahli sunna wal-Jamaa, kalam, Moturidism, leader, Ash'ariism, teacher, creed, region, teaching, silsila, shahabcha, ta'wilat.